PENERAPAN METODE SAW UNTUK PEMILIHAN WILAYAH RT PENERIMA BANTUAN WIFI SEBAGAI SARANA PENDUKUNG PEMBELAJARAN DI MASA PANDEMI - Frederik Aristaputra; Moh Bhanu Setyawan; Angga Prasetyo (KOMPUTEK, 2022)
Wireless Fidelity (Wi-Fi) is a medium that delivers data communication with great capabilities and without the need for cables as fast connectors. During the Covid-19 Pandemic, many school children had to do Brave learning because of this, many people were not ready with this learning method, therefore problems would occur in household economic conditions. This research was conducted in the Chilian village, Sawahan sub-district, Madiun district in the application of the SAW method for the selection of RT areas receiving wifi assistance as a means of supporting learning during the pandemic. This study uses the SAW method because this method has been proven to help in overcoming the decision-making problems in this study. The result of this study is that the SAW method has been successfully applied to support the decision to select RT areas as recipients of WiFi assistance in order to support learning during the pandemic in Cabean Village, Sawahan District, Madiun Regency, East Java.